Geomorphological study of Kleinovitikos stream drainage network (Trikala prefecture - western Thessaly) - Bathrellos, G. D.; Skilodimou, H. D.; Livaditis, G.; Verikiou-Papaspiridakou, E. (Bulletin of the Geological Society of Greece, 2007)
The Kleinovitikos stream is a tributary ofPineios River in the Western Thessaly. Its basin drainages parts of mountain range of Southern Pindos as well as the mountain of Koziaka. In this study a quantitative analysis of drainage network was accomplished and the relation of tectonics features with the watershed and the channels of drainage network were investigated. The main channel of the drainage network is of 6th order, while the dominated type of the network is the trellis drainage pattern. The morphological slopes of the basin show various fluctuations. The gentle slopes express erosional landforms while the steep ones represent geological and tectonic structures. It was noted by the quantitative analysis of the drainage network that the geological and tectonic structure of the area affects in its evolution. Moreover, the outcrop of heterogeneous lithological formations in the basin affects the values of drainage density and frequency. The lithology and the secondary cracks involve in the prevailing direction of the watershed. The streams of 1st -3r order are controlled by the younger cracks; the younger cracks as well as the older Alpine cracks have an influence on the streams of 4' and 5' order, and the Alpine tectonic activity affects the stream of 6' order.